LEONARDO DICAPRIO'S MOVEMENT AND COMBAT AGAINST CLIMATE CHANGE ON HIS U.N. SPEECH - Maharani, Amanda Vira (Salingka, 2019)
Leonardo DiCaprio was chosen as United Nations Messenger of Peace in 2014 and gave speech in the Paris Agreement on the U.N. This research aim to find out how climate change described on the lexical choices used by Leonardo DiCaprio on his U.N. speech to convey his ideology. This research uses qualitative research design with critical discourse analysis approach proposed by Norman Fairclough. The data of this research is Leonardo DiCaprio’s speech at the opening of Signature Ceremony for the Paris Agreement by the U.N. The result is his ideology is represented on his lexical choices, which are positive and negative representation that describes his movement and combat against the climate change that represents on his U.N. speech as Messenger of Peace on climate change.